Pharmacology and Nutritional Intervention in the Treatment of Disease - Atroshi, Faik; Atroshi, Faik (IntechOpen, 2014)
Pharmacology and Nutritional Intervention in the Treatment of Disease is a book dealing with an important research field that has worldwide significance. Its aim is to strengthen the research base of this field of investigation as it yields knowledge that has important implications for biomedicine, public health and biotechnology. The book has brought together an interdisciplinary group of contributors and prominent scholars from different parts of the world. The basic purpose of this book was to promote interaction and discussion of problems of mutual interests among people in related fields everywhere. The main subjects of the book include nutrition, mechanisms underlying treatments, physiological aspects of vitamins and trace elements, antioxidants: regulation, signalling, infection and inflammation, and degenerative and chronic diseases.
English
Keywords: Neurology & clinical neurophysiology; Neurology & clinical neurophysiology